Le genre du prêt sur gage : rapports de pouvoir au Mont-de-Piété de Paris (années 1850 – années 1920) - Anaïs Albert (Genre & Histoire)
The Mont-de-Piété of Paris was a public pawnbroking institution, founded in 1777 in order to fight against usury. It played a crucial role in the economy of the capital city, especially for the working classes who often owned only their movable goods. But the engagements–that is the exchange of an object against a sum of money–were predominantly performed by women. These engagements formed part of women’s domestic strategies in working-class households. Female servants in bourgeois households pawned possessions for their masters as well. In contrast, only a few upper-class women ventured the risk. At the Mont-de-Piété, female borrowers would face male clerks, particularly the auctioneers, who came from the upper-classes and held a monopoly on the valuation of goods. The analysis of pawnbroking reveals the way it represented an economic power struggle in which gender and class dynamics shaped the framework of the exchange.